Usability evaluation of information systems in public administration based on the fuzzy approach - Zatloukal, Michal (Univerzita Pardubice, 2009)
This diploma work presents a new methodology of usability evaluation based on the principles of fuzzy theory. Unlike the other methods allows obtaining a score of usability evaluation. Although the methodology is designed to evaluate the usability of information systems in public administration, it might be generally used for any kind of user interface. The usability score represents a meaningful and authentic value - an indicator of quality of particular information system, a value that can be compared with the others.
Fuzzy modelování při hodnocení použitelnosti informačních systémů veřejné správy
Keywords: Usability; Information Systems; Public Administration; fuzzy logic; Quality; software engineering; Použitelnost; Informační systémy; fuzzy logika; Kvalita; softwarové inženýrství; veřejná správa